Probing negative ions and electrons in the afterglow of a low-pressure oxygen radiofrequency plasma using laser-induced photodetachment. (13th September 2021) - Hasani, M; Marvi, Z; Beckers, J
Abstract: This paper reports on the further development and improvement of time-resolved laser-induced photodetachment in concert with microwave cavity resonance spectroscopy. The method is applied to measure—with microsecond time resolution—the decaying density of negative oxygen ions (O −, O 2 −, and O 3 − ) and that of free electrons in the afterglow of a pulsed capacitively coupled radiofrequency-driven oxygen plasma. The afterglow behavior of the electrons shows a significant dependence on the gas pressure between 3 Pa and 6 Pa. For a pressure of 3 Pa, at which the plasma is in the so-called γ -mode, the decay of the negative ion density is slower than that of the electron density, eventually leading to the occurrence of a negative-ion-positive-ion plasma. At a slightly elevated pressure of 6 Pa (and higher), the plasma transits into the so-called α -mode, in which a short period of increased electron density is detected just after switching off the plasma. In the α -mode, the negative ion and electron densities decay within similar timescales, leading to the trapping of negative ions. In this pressure range, the decay of the additional electron density released by the photodetachment of negative ions occurs according to two distinct timescales. However, for increasingly elevated pressures above 10 Pa, the photodetachment signal is characterized by decay with an undershoot, which may indicate a temporary local disturbance of the plasma's quasi-neutrality in the volume irradiated by the laser beam.